Increasing student engagement and retention using immersive interfaces virtual worlds, gaming, and simulation - Wankel, Laura A.; Blessinger, Patrick (Bingley, U.K. : Emerald, 2012)
Increasing Student Engagement and Retention Using Immersive Interfaces: Virtual Worlds, Gaming, and Simulation uses case studies, surveys, and literature reviews to critically examine how gaming, simulation, and virtualization are being used to improve teamwork and leadership skills in students, create engaging communities of practice, and as experiential learning tools to create inter-cultural, multi-perspective, and global experiences. Chapters include how to increase learner engagement using serious games, using game features for classroom engagement, using client-based peer assessment in multi-role, whole-enterprise simulations, using virtual worlds to develop teacher candidate skills, enhancing leadership skills through virtual simulation, using online video simulation for educational leadership, using augmented reality in education, using open source software in education, using educational robotics laboratories to enhance active learning, and utilizing the virtual learning environment to encourage faculty reflection. This volume will also discuss a framework for deploying and assessing these technologies.
Innovative approaches in higher education : an introduction to using immersive interfaces / Patrick Blessinger, Charles Wanke -- Learner engagement in the use of individual and collaborative serious games / Margarida Romero -- Strategies for designing engaging e-learning instructions : know your learners' need / Wei Lian Tan -- Game mechanics for classroom engagement / Stayc DuBravac -- Increasing student engagement using client-based peer assessment in multi-role, whole-enterprise simulations / Steve Gove -- Bringing the classroom to life : using virtual worlds to develop teacher candidate skills / Danielle Mirliss, Grace May, Mary Zedeck -- Engaging Chinese students and enhancing leadership development through virtual simulation : a cross-cultural perspective / Scott A. Johnson, Jing Luo -- Engagement in an online video simulation in educational leadership / R. Martin Reardon ... [et al.] -- Augmenting engagement : augmented reality in education / Jon Cabiria -- Bolstering student hands-on experience through the use of virtualization / Denise M. Pheils -- Use of open source software and virtualization in academia to enhance higher education everywhere / Maurice Eugene Dawson, Imad Al Saeed -- Active learning in a robotics laboratory with university students / Lorella Gabriele, Assunta Tavernise, Francesca Bertacchini -- Utilising the virtual learning environment to encourage faculty reflection and improve the student learning experience / Tiffany M. Winchester, Maxwell K. Winchester.
Includes index.
Print version record
Keywords: Education -- Computers & Technology; Education -- Distance Education & Learning; Teachers' classroom resources & material; Educational: IT & computing, ICT; Internet in higher education; Education, Higher -- Simulation methods; Virtual reality in education; Simulation games in education